A Putative Functional Variant Within the UBAC2 Gene Is Associated With Increased Risk of Behcet's Disease - DİRESKENELİ, RAFİ HANER (WILEY-BLACKWELL, 2011)
Objective. Using a genome-wide association scan and DNA pooling, we previously identified 5 novel genetic susceptibility loci for Behc,et's disease. We undertook this study to establish the genetic effect within the UBAC2 gene, in the course of which we replicated this genetic association and identified a functional variant within this locus. Methods. We studied a total of 676 Behcet's disease patients and 1,096 controls. The discovery set included 156 patients and 167 controls from Turkey, and the replication sets included 376 patients and 369 controls from Turkey and 144 patients and 560 controls from Italy. Genotyping of 14 single-nucleotide polymorphisms (SNPs) within and around UBAC2 was performed using TaqMan SNP genotyping assays. Results. The genetic association between Behc, et's disease and UBAC2 was established, replicated, and confirmed (meta-analysis odds ratio 1.84, P = 1.69 x 10(-7)). Haplotype analysis identified both a disease-risk haplotype and a protective haplotype (P = 0.00014 and P = 0.0075, respectively). Using conditional haplotype analysis, we identified the SNP rs7999348 (A/G) within UBAC2 as the most likely SNP with a genetic effect independent of the haplotypic effect formed by the remaining associated SNPs in this locus. Indeed, we demonstrated that rs7999348 tags a functional variant associated with increased messenger RNA expression of a UBAC2 transcript variant in peripheral blood mononuclear cells of individuals homozygous for the Behc, et's disease-associated G allele. Further, our data suggested the possibility of multiple genetic effects that increase susceptibility to Behc, et's disease in the UBAC2 locus. Conclusion. We established and confirmed the genetic association between UBAC2 and Behcet's disease in 3 independent sets of patients and controls. We identified the minor allele in rs7999348 as a disease-risk allele that tags altered UBAC2 expression.
Keywords: GENOME-WIDE ASSOCIATION; SUSCEPTIBILITY LOCI; IL23R-IL12RB2; VISUALIZATION; PREVALENCE; SEVERITY; IL10; AGE